GoScreen: Application to help medical students learn the practical of health screening - Norwati, Daud; Nurulhuda, Mat Hassan (2018)
Highlights: According to Health Facts 2017, cardiovascular disease and cancer are the major cause of death and admission in Malaysian hospitals. Healthcare staff’s recommendation is a powerful factor for public to undergo screening. Prevention and screening is one of the topics taught during family medicine course in medical programme. Since medical students usually see patients who already have the diseases, learning on what to screen on asymptomatic patients maybe opportunistic. The use of an application may help students to practise on the decision on health screening to asymptomatic patients. The application will analyse the clinical information and recommend specific health screening. With repeated practice, students will learn on practical screening based on each individual patient’s background.